2018
DOI: 10.1016/j.cell.2017.12.030
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Structure of Neuronal C9orf72 Poly-GA Aggregates Reveals Proteasome Recruitment

Abstract: Summary Protein aggregation and dysfunction of the ubiquitin-proteasome system are hallmarks of many neurodegenerative diseases. Here we address the elusive link between these phenomena employing cryo-electron tomography to dissect the molecular architecture of protein aggregates within intact neurons at high resolution. We focus on the poly-Gly-Ala (GA) aggregates resulting from aberrant translation of an expanded GGGGCC repeat in C9orf72, the most common genetic cause of amyotrophic lateral sclerosis and fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
317
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 351 publications
(354 citation statements)
references
References 96 publications
22
317
3
Order By: Relevance
“…This observation could also be explained by the presence of active proteasomes within the phagosomal/endolysosomal lumen. Recent cryo-electron microscopy analysis has shown that proteasomes localize to the cytosol and cytosolic protein aggregates in neuronal cells (Asano et al, 2015;Guo et al, 2018). TAP-Like (TAP-L), a TAP homologue localized to lysosomal membranes, has been suggested as a candidate, although it was recently shown that BMDC derived from TAP-L knockout mice do not exhibit impaired cross-presentation (Lawand et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation could also be explained by the presence of active proteasomes within the phagosomal/endolysosomal lumen. Recent cryo-electron microscopy analysis has shown that proteasomes localize to the cytosol and cytosolic protein aggregates in neuronal cells (Asano et al, 2015;Guo et al, 2018). TAP-Like (TAP-L), a TAP homologue localized to lysosomal membranes, has been suggested as a candidate, although it was recently shown that BMDC derived from TAP-L knockout mice do not exhibit impaired cross-presentation (Lawand et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of proteasome substrates identified have been cytosolic, nuclear, or membrane proteins. Recent cryo-electron microscopy analysis has shown that proteasomes localize to the cytosol and cytosolic protein aggregates in neuronal cells (Asano et al, 2015;Guo et al, 2018). However, studies in yeast and plant cells have shown that endocytic compartments contain proteasomes, although no evidence was presented that they were active (Marshall et al, 2015;Cohen-Kaplan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, poly-GA is highly aggregation-prone, presumably due to its hydrophobic nature. Electron microscopy studies of cerebellar granule cells from a C9orf72 -FTD/ALS patient showed that poly-GA NCIs contain 15–17 nm filamentous structures [174], but a more recent study using cryo-electron tomography showed that poly-GA aggregates in cultured neurons are made up of densely packed twisted 13–15 nm thick ribbons with varying length and width [52]. Further understanding of the ultrastructural featuresof DPR aggregates could shed light on toxicity mechanisms and guide therapeutic development.…”
Section: Clinical and Anatomical Features Of C9orf72-ftd/alsmentioning
confidence: 99%
“…Primary hippocampal cultures were prepared from E19 rats as described previously and plated on glass coverslips coated with ª 2018 The Authors EMBO Molecular Medicine 10: e8558 | 2018 poly-D-lysine (Guo et al, 2018). Lentivirus was packaged in HEK293FT cells as described (Guo et al, 2018).…”
Section: Neuronal Cell Culture and Lentivirus Productionmentioning
confidence: 99%